PERSONNEL PERFORMANCE ASSESSMENT INFORMATION SYSTEM AT PT. ABDI GABE USING BARS METHOD - JONAS FRANKY RUDIANTO PANGGABEAN; Kamson Sirait (Jurnal Mantik, 2021)
In today's world of work, performance appraisal of personnel in a company is very important, because it relates to company decision making on the performance of company personnel. PT ABDI GABE is a food ingredient sales company, where the company does not yet have clear standards on personnel performance appraisal tests, thus causing an unfavorable impact on company personnel who only consider it a formality in personnel performance appraisals. As a result of not having proper standards, many company personnel do not have work standards and do not have the motivation to develop the company. To overcome the problems that occur in PT. ABDI GABE, the author is interested in developing a method for evaluating the performance of company personnel using the Behaviorally Anchor Rating Scale (BARS) method, this method can help companies support personnel performance appraisal decisions, so as to get the results of personnel performance appraisals according to standards that will make personnel comfortable and motivated. in the progress of the company.